Pengaruh Work-life balance, Motivasi, Self-efficacy, dan Kompensasi terhadap Kepuasan Kerja pada Generasi Z di Kota Surabaya - Dani, Nasrul; Asnawi, Anita; Arfani, Mochammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the influence of motivation, work-life balance, self-efficacy, and compensation on the job satisfaction of Generation Z in Surabaya. Using a quantitative descriptive method, this study utilizes primary data obtained through questionnaires to analyze the relationship between variables. The 100 respondents were dominated by men with high school/vocational education, most of whom worked in the private sector, with fields of work that matched their skills. The results of the partial influence test showed that each of the motivation, self-efficacy, and compensation factors had a significant and positive influence on job satisfaction, indicating these factors play important roles in creating job satisfaction in Generation Z in Surabaya. Meanwhile, the compensation factor is responded to as the main factor in realizing job satisfaction. In contrast, work-life balance did not have a significant effect, indicating that respondents considered that they had not found a balance in managing their time between life and work, so their job satisfaction could not be realized based on the factors that set the time balance. On the other hand, simultaneously, these four variables have a significant influence on job satisfaction.